Training characteristics in highly treined athletes - Ricardo dos Santos; Aurineider Marcelino da Silva; Glaycon Michels (Journal of Physical Education (Maringá), 2008)
The adaptation to the training seems to depend on factors such as: intensity of the training volume, frequency and initial level of physical aptitude. However, in highly trained athletes, the intensity of the training and the initial level of performance seem to be the most important main factors influencing the reply to the training and, therefore the performance of the competition considering that the volume of necessary training and the frequency are assured. During the training preparation for an important competition, the athletes tend to reduce the training load for a period of variable time. The technique, known as “taper” (reduction), may have bigger influence on the athletes’ performance. The reply to this reduction may be affected by the degree which the intensity of training volume and frequency is reduced by, as well as by the agreed effect of these variables. A literature revision suggests that the volume of training and the frequency may be reduced to a bigger level than the training intensity, a production fall should be prevented. The duration of the period of reduction and the constant time of fall of the training load may affect the reply of this reduction.